The Influence of Store Atmosphere, Perceived Price, and Customer Experience on Repurchase Intention at Niceso Rungkut Surabaya - Alam, Hakim Bima Ardimas; Purwanto, Sugeng (East Asian Journal of Multidisciplinary Research, 2024)
The advancement of modern technology and economic growth have made Indonesia a very potential retail market, especially in the modern retail sector. In addition, retail competition is also increasing with the presence of foreign retailers competing with domestic retailers. The domestic retail industry in question is Niceso. The purpose of this research is to understand the reasons for purchase, perceptions of Niceso, and the level of consumer desire in influencing repeat purchase behavior at the store. This research employs a quantitative research method, and the measurement of variables is conducted using a Likert scale. The sampling technique uses non-probability sampling through a convenience sampling approach, and the sample size obtained is 102 respondents. The data analysis technique used is the PLS (Partial Least Square) method. This method is used to conduct validity and reliability tests, structural model, and hypothesis testing from the existing data. The results of this study indicate that store atmosphere, perceived price, and customer experience each contribute and have a significant influence on the repurchase intention of Niceso Rungkut Surabaya consumers.